Supportive functions of soil organic carbon for ecosystem services in karst desertification areas - Wang Xingfu; Liu Yi; Xiong Kangning; Huang Xianfei; Zhang Zhenming (Ecological Indicators)
In this study, we explored the supportive functions of soil organic carbon (SOC) for ecosystem services in karst rocky desertification areas. A total of 200 soil samples were taken from various land use types, including grassland, forest and, agroforestry, and bare land in each rocky desertification location. The total SOC and its fractions, nitrogen (TN), phosphorus (TP), and potassium (TK) concentrations and the soil moisture were measured. The ecosystem service functions of soil nutrient retention, soil conservation, and carbon balance responses to the SOC were analyzed. The trade-off/synergy relationship between all the factors was discussed, and the shortcomings of the different ecosystems were identified. Finally, an optimization model with high synergy between each ecosystem service was proposed. The results showed that the SOC varies greatly under different rocky desertification levels, with values ranging from 11.28 to 35.08 g·kg−1 and a mean of 23.80 g·kg−1. The SOC content in the different rocky desertification levels was as follows, in descending order: moderate to intense > potential to mild > nonexistent to potential. Meanwhile, the SOC content in the different ecosystems was as follows, in descending order: agroforestry land > forest land > grassland. The values range of TN, TP, and TK were 1.04 to 2.95, 0.38 to 1.29, and 1.17 to 13.60 g·kg−1 respectively, and their average values were 2.01, 1.06, and 5.37 g·kg−1. The SOC can promote the benefits of TN, TP, and TK, prevent erosion, and improve soil moisture and carbon storage to a certain extent. There was a high synergy between each of the factors in the soil of the agroforestry ecosystems, especially SOC, TN, and TP in the nonexistent to potential rocky desertification area. The agroforestry models “forest-grain”, “forest-fruit”, “forest-vegetable” and “forest-medicine” can be used as extension models of the artificial ecosystem, which can promote ecosystem service synergy and the comprehensive control of rocky desertification in the South China Karst.